ALTERNATIVE SETTLEMENT SYSTEM IN THE FUEL AND ENERGY COMPLEX: CLASSIFICATION AND MAIN FEATURES - O. Baikova; D. Kulakov (Вестник университета)
Marks need of increase of economic security and marked out threats to the Russian economy from «petrodollars». Сonsidere Classification of impecunious contracts, substantiations the key purposes and problems of active application of methods of the alternative estimation of cost of energy carriers excluding a monies as equivalent in the conditions of world financial-political crisis and the anti-Russian sanctions are proved. Characteristics of functions of fuel and energy resources is submitted as goods. Marked out Features of trade within fuel and energy complex of the Russian Federation. Revealed Possibilities of activization of innovative development of resource trade as one of the main methods of increase of security both fuel and energy complex, and all Russian economics.